KESANTUNAN BERBAHASA DALAM INTERAKSI ANTARMASYARAKAT DESA KAMPUNG TARANDAM GURUN PANJANG SELATAN KECAMATAN BAYANG KABUPATEN PESISIR SELATAN - Rela Karnila; Zuraida Khairani; Eva Fitrianti (Ekasakti Educational Scientific Journal, 2025)
This research began with the researcher's observation of the form of politeness in language in Inter-Community Interaction in Kampung Tarandam Gurun Panjang Selatan Village, Bayang District, Pesisir Selatan Regency. The language used by the people of Kampung Tarandam Village is diverse, for example in the use of the word kau/waang, some people use the word and understand that the word is impolite. While some people say that the word kau/waang can be said to be polite if the interlocutor is someone of the same age and the interlocutor is not angry or offended if called kau/waang. The purpose of this study is to describe the form and meaning of politeness in the language of the people of Kampung Tarandam, Gurun Panjang Selatan, Pesisir Selatan. This type of research is qualitative, research that produces descriptive data in the form of written words, spoken words from people and observable behavior. The method used in this study is a descriptive method. Data collection techniques in this study are observation, documentation, listening techniques, recording, taking notes. Data analysis techniques in this study are data collection, data reduction, data presentation and conclusions. The results of this study indicate that the form and meaning of politeness in language in Inter-Community Interaction in Kampung Tarandam Gurun Panjang Selatan Village, Bayang District, Pesisir Selatan Regency obey the maxims of wisdom, generosity, sympathy, humility, and agreement. Of the five maxims, wisdom, generosity, sympathy, humility, and agreement, there are two maxims that are predominantly used by the people of Kampung Tarandam Gurun Panjang Selatan Village, Bayang District, Pesisir Selatan Regency. The maxims that are often used are the maxim of wisdom and the maxim of agreement